Children's online privacy protection: a comparative study between the acts in Malaysia with the Children's Online Privacy Protection Act (COPPA) 1998 / Nur Fasihah Shahrol Azam, Nur Izzati Mohd Hamdi and Nabila Abdullah. - Shahrol Azam, Nur Fasihah; Mohd Hamdi, Nur Izzati; Abdullah, Nabila (Faculty of Law, 2013)
Children and young people are among the internet users whom would constantly utilize the internet in various ways. Young people's private lives are increasingly laid bare by the often personal data published in their blogs, on social networks, in chat rooms, and so on. At a very young age, web users face some complex issues: copyright on the Internet, image rights, protection of personal data and private life, and the risks inherent in the Internet's new social forums. Although there are many laws that defines, govern and protect the activity of children and their legal rights and their online activity of the Malaysian internet users, none of them fills in the need of protection of the children's online privacy protection. Thus, in enhancing the laws that has been implemented, several provisions need to be inserted to overcome this lacuna. The United States of America had taken steps to resolve this issue, hence are made as reference to improve the laws regarding the protection of online data of the children.